A Rare Case of Paraneoplastic Syndrome Presented with Severe Gastroparesis due to Ganglional Loss. (4th December 2012) - Argyriou, Konstantinos N.; Peters, Martin; Ishtiaq, Javaid; Enaganti, Santosh
Abstract : Paraneoplastic syndromes are rare initial manifestations of a neoplastic disorder that may precede the actual detection of an overt cancer. These syndromes can generally involve any organic system of the human body with gastroparesis being the commonest manifestation of the paraneoplastic involvement of the neuronal bodies of the gastrointestinal tract in cancer patients. Gastroparesis is the result of an autoimmune destruction of the nerve plexus of the stomach that causes nonspecific gastrointestinal symptoms such as intractable vomiting and abdominal discomfort that interfere with patients' quality of life and are often ascribed to psychological factors. Thus, if not suspected, it easily evades the diagnostic thought especially in those cases where the diagnostic work up has not detected any apparent cause. Consequently, it should always be considered in patients with diagnosed or suspected cancer who complain of unexplained gastrointestinal symptoms. In our report, so as to increase the clinical awareness of this rare clinical entity, we present the case of a 70-year-old Caucasian female who presented in our hospital with severe gastroparesis that was later proven to be associated with an overt small cell lung cancer (SCLC) and we discuss the existing knowledge of the pathophysiology, diagnosis, and management of this disorder.